Contrasting effects of polysaccharide components on the cooking properties of Roots, Tubers and Bananas (RTBs) - Mestres, C.; Taylor, M.; McDougall, G.; Arufe, S.; Tran, T.; Nuwamanya, E.; Dufour, D.; Nakitto, M.; Meghar, K.; Rinaldo, D.; Ollier, L.; Domingo, R.; et al. (Wiley, 2024)
Background: Consumer preferences for boiled or fried pieces of roots, tubers and bananas (RTBs) foodstuffs are mainly related to their texture. Different raw and cooked RTBs were physiochemically characterised to determine the effect of biochemical components on their cooking properties.